2018
DOI: 10.5194/cp-14-825-2018
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanisms of warming the mid-Pliocene and the inference of a hierarchy of climate sensitivities with relevance to the understanding of climate futures

Abstract: Abstract. We present results from our investigation into the physical mechanisms through which the mid-Pliocene, with a pCO2 of only  ∼  400 ppmv, could have supported the same magnitude of global warmth as has been projected for the climate at the end of the 21st century when pCO2 is expected to be 3 times higher. These mechanisms allow us to understand the warming in terms of changes to the radiative properties of the surface, the clouds, greenhouse gases, and changes to the meridional heat transport. We fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 80 publications
5
45
0
Order By: Relevance
“…3.3-3.0 Ma BP) and before. Although spatial details of the mega-lake system are not known, Chen and Bowler (1986) reported that the total lake surface was about 59 000 km 2 during the early Pleistocene. The onset of the Pleistocene glaciations at ca.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3.3-3.0 Ma BP) and before. Although spatial details of the mega-lake system are not known, Chen and Bowler (1986) reported that the total lake surface was about 59 000 km 2 during the early Pleistocene. The onset of the Pleistocene glaciations at ca.…”
Section: Introductionmentioning
confidence: 99%
“…This approach follows the general idea underlying studies that have linked climates of the past with those projected for the near future using the concept of climate sensitivity (e.g. Chandan and Peltier, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even for changes as recent as the mid-Holocene, there is a debate, for example, over whether the abrupt desertification of the Sahara is due to a bifurcation, as suggested in Claussen et al (1999) using an Earth model of intermediate complexity (EMIC), or is a transient response of the AMOC to a sudden termination of freshwater discharge to the North Atlantic, as proposed in Liu et al (2009), using a coupled atmosphere-ocean GCM (AOGCM). Similarly, for the glaciation of Greenland at the Pliocene-Pleistocene transition, recent work in Tan et al (2018), using a coupled GCM-ice-sheet model, shows good agreement with proxy records without the need for bifurcations.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, the Pliocene is considered a potential analog for climate conditions predicted for the latter part of this century (Crowley, 1996;Dowsett et al, 1996;Dowsett & Robinson, 2009). Not surprisingly, Pliocene climate model simulations with concentrations of CO 2 greater than those of pre-industrial time (Burls et al, 2017;Chandan & Peltier, 2018, 2017Haywood et al, 2010Haywood et al, , 2013Lunt et al, 2008;Salzmann et al, 2013) and/or with assumed or simulated reduced northern hemisphere ice cover (e.g., Feng et al, 2017;Haywood & Valdes, 2004;Howell et al, 2016) lead to higher temperatures at mid and high latitudes. Other model runs, however, that exploit perturbations to equatorial Pacific SSTs can also lead to warmer midlatitude and high-latitude (e.g., Barreiro et al, 2005;Brierley & Fedorov, 2010;Burls & Fedorov, 2014a, 2014bGoldner et al, 2011;Shukla et al, 2009Shukla et al, , 2011Vizcaíno et al, 2010).…”
Section: Introductionmentioning
confidence: 99%